Disease-Associated Variants in GRIN1, GRIN2A and GRIN2B genes: Insights into NMDA Receptor Structure, Function, and Pathophysiology - Korinek, M; Candelas Serra, M; Abdel Rahman, Fes; Dobrovolski, M; Kuchtiak, V; Abramova, V; Fili, K; Tomovic, E; Hrcka Krausova, B; Krusek, J; Cerny, J; Vyklicky, L; et al. (Physiological research, 2024)
N-methyl-D-aspartate receptors (NMDARs) are a subtype of ionotropic glutamate receptors critical for synaptic transmission and plasticity, and for the development of neural circuits. Rare or de-novo variants in GRIN genes encoding NMDAR subunits have been associated with neurodevelopmental disorders characterized by intellectual disability, developmental delay, autism, schizophrenia, or epilepsy. In recent years, some disease-associated variants in GRIN genes have been characterized using recombinant receptors expressed in non-neuronal cells, and a few variants have also been studied in neuronal preparations or animal models. Here we review the current literature on the functional evaluation of human disease-associated variants in GRIN1, GRIN2A and GRIN2B genes at all levels of analysis. Focusing on the impact of different patient variants at the level of receptor function, we discuss effects on receptor agonist and co-agonist affinity, channel open probability, and receptor cell surface expression. We consider how such receptor-level functional information may be used to classify variants as gain-of-function or loss-of-function, and discuss the limitations of this classification at the synaptic, cellular, or system level. Together this work by many laboratories worldwide yields valuable insights into NMDAR structure and function, and represents significant progress in the effort to understand and treat GRIN disorders. Keywords: NMDA receptor , GRIN genes, Genetic variants, Electrophysiology, Synapse, Animal models.
Keywords: Neurodevelopmental Disorders; genetická variace; receptory N-methyl-D-aspartátu; Genetic Variation; proteiny nervové tkáně; Animals; Receptors, N-Methyl-D-Aspartate; Humans; lidé; zvířata; Nerve Tissue Proteins; Genetic Predisposition to Disease; genetická predispozice k nemoci; neurovývojové poruchy